Does Our Gut Microbiome Predict Cardiovascular Risk?: A Review of the Evidence From Metabolomics. (February 2015) - Griffin, Julian L.; Wang, Xinzhu; Stanley, Elizabeth
Abstract : Millions of microbes are found in the human gut, and are collectively referred as the gut microbiota. Recent studies have estimated that the microbiota genome contains 100-fold more genes than the host genome. These microbiota contribute to digestion by processing energy substrates unutilized by the host, with about half of the total genome of the gut microbiota being related to central carbon and amino acid metabolism as well as the biosynthesis of secondary metabolites. Therefore, the gut microbiome and its interaction with the host influences many aspects of health and disease, including the composition of biofluids such as urine and blood plasma. Metabolomics is uniquely suited to capture these functional host-microbe interactions. This review aims at providing an overview of recent metabolomics evidence of gut microbiota-host metabolic interactions with a specific focus on cardiovascular disease and related aspects of the metabolic syndrome. Furthermore, the emphasis is given on the complexities of translating these metabolite signatures as potential clinical biomarkers, as the composition and activity of gut microbiome change with many factors, particularly with diet, with special reference to trimethylamine-oxide.